Otoplastik Otoplasty - Heppt, Werner; Springer Electronic Media (Berlin : Springer, 2000)
(Producer) Offers a bilingual interactive guide through anesthetic and reconstructive otoplasty. Animations, interactive links, and an interactive operative training program provide everything that is needed in daily practice including tips and tricks, dos and don'ts, and complication management
Title from disc label
Editors, Werner Heppt, et al.
System requirements: Processor, 133 MHz; 32 MB Ram; Microsoft Windows 95/98/2000, ME or NT (4.0 or later); 800 x 600 display; 16 bit; 4-speed CD-ROM
In English and German
Keywords: Ear, External -- surgery; Reconstructive Surgical Procedures -- methods